A Comparison of the Ability Emotional Intelligence of Head Teachers With School Teachers in Other Positions - Gutiérrez-Cobo, María José; Cabello, Rosario; Rodríguez-Corrales, Juan; Megías-Robles, Alberto; Gómez-Leal, Raquel; Fernández-Berrocal, Pablo (Frontiers in Psychology, 2019)
Head teachers are exposed to a highly emotional and stressful job, and they need a sufficient combination of professional competencies in order to deal with daily challenges in schools. Recent studies have shown the importance of developing emotional competencies such as Emotional Intelligence (EI) in teachers in order to improve their professional development and to ensure the adequate functioning of the school. However, rather less is known about the ability EI of head teachers. The aim of the present study was to evaluate the ability EI of public school head teachers and compare this ability with those working in other positions within the school. For these purposes, 393 participants (35 head teachers, 39 middle leaders, 236 tutors, and 86 teachers) aged between 24 and 62 years (M = 40.26; SD = 9.27) completed the Mayer-Salovey-Caruso Emotional Intelligence Test (MSCEIT). The results revealed a significantly higher total EI for head teachers than teachers, along with higher scores in the understanding branch of the MSCEIT for the head teachers compared with workers in other positions. In addition, on this EI branch, tutors also achieved higher scores than the teachers. We also evaluated the alternative hypothesis that years of teaching experience could explain the relationship between work position and the EI scores, and found no evidence in support of this possibility. Limitations and future lines of research are discussed.